Effect of Changing Particle Diameters in Porous Media on Heat Transfer Coefficient for Three-Phase Flow in Vertical Pipe. (Journal of University of Babylon for Engineering Sciences, 2018)
The paper is dedicated to of study heat transfer coefficient of three-phase mixture through porous media 20 cm length, the packaging material made of chrome-steel used are 2, 6 and 10mm and its carried out in Perspex vertical pipe 3.175 cm diameter and overall length of 2 m .The gasoil, water and air used as working fluids. The heat transfer coefficient values for 2mm case is higher than 6, 10 mm cases because of higher thermal conductivity for small particle diameter. It observed the inversely relationship between the heat transfer coefficient and particle diameters. In addition, it observed that porous media region has a minimum value because damping in velocity through it. Also, it found the heat transfer coefficient  values increase with increase temperature of water phase Simulation results by using computational fluid dynamics CFD building a modeler using VOF model .The volume of fluid VOF approach is used to simulate the flow in porous media with three-sizes of particles respectively. The deviation between results with other researchers was acceptable is about 17.04 %.